2019
DOI: 10.1021/acs.jnatprod.9b00493
|View full text |Cite|
|
Sign up to set email alerts
|

Lamellarin Sulfates from the Pacific Tunicate Didemnum ternerratum

Abstract: Six new lamellarin sulfates (1–6) were isolated from the methanolic extract of the Pacific tunicate Didemnum ternerratum, collected from the Kingdom of Tonga. Mass spectrometric molecular networking through the GNPS platform was used to target the isolation of 1–6. Planar structures were elucidated through a combination of NMR and MS experiments. Through comparison of experimental and calculated ECD spectra, the absolute configurations of atropisomers 2–5 were determined, with their energetic barriers to racem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…[1] Some authors, familiar with the contents of the original publication, have applied or quoted this correctly. [2][3][4][5][6][7] Unfortunately, the first easily located publication [8] using the term Crews' rule gives the critical H/C atom ratio as 2 rather than the value of 1 given in the original paper. This error has propagated through the literature [9][10][11][12][13][14][15][16][17][18] and continues to do so to this day.…”
mentioning
confidence: 99%
“…[1] Some authors, familiar with the contents of the original publication, have applied or quoted this correctly. [2][3][4][5][6][7] Unfortunately, the first easily located publication [8] using the term Crews' rule gives the critical H/C atom ratio as 2 rather than the value of 1 given in the original paper. This error has propagated through the literature [9][10][11][12][13][14][15][16][17][18] and continues to do so to this day.…”
mentioning
confidence: 99%
“…24(R)-methylcholest-6-en-3β-ol (38), 5α,8α-epidioxy-24(S)-ethylcholest-6-en-3β-ol (39), and 5α,8αepidioxy-24(R)-ethylcholest-6-en-3β-ol (40) [24]. Bromley and co-authors have reported two halogenated compounds from a South African unidentified Didemnum sp., namely 3,5dibromotetramethyltyrosine (41) and 3-iodotetramethyltyrosine (42) (Figure 8) [25].…”
Section: Secondary Metabolites With No Currently Reported Bioactivitymentioning
confidence: 99%
“…Five 5α,8α-epidioxysterols derivatives were isolated from D. salary including 5α,8αepidioxycholest-6-en-3β-ol (36), 5α,8α-epidioxy-24(S)-methylcholest-6-en-3β-ol (37), 5α,8α-epidioxy-24(R)-methylcholest-6-en-3β-ol (38), 5α,8α-epidioxy-24(S)-ethylcholest-6-en-3β-ol (39), and 5α,8αepidioxy-24(R)-ethylcholest-6-en-3β-ol (40) [24].…”
Section: Secondary Metabolites With No Currently Reported Bioactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our continuing investigation of the secondary metabolites produced by marine invertebrates collected from the South Pacific [10][11][12][13], we recently reported the first study utilizing MN to examine the chemical constituents of various Tongan marine tunicates [14]. The major constellation of the network consisted of three linked clusters of nodes, and prioritization of the fractions containing lamellarin sulfates resulted in the characterization of the first new sulfated lamellarins reported in over 20 years [14]. Tunicates have been an excellent source of natural products to date, including the FDA-approved plitidepsin (Aplidin ® ) and trabectedin (Yondelis ® ); however, the number of new tunicate-derived compounds reported annually is decreasing, with 45% less reported in 2017 compared to 2016 [15].…”
Section: Introductionmentioning
confidence: 99%